Enhancing Water Resource Management Efficiency through Smart Technologies: A Case Study in Kashkadarya Region, Uzbekistan: Meningkatkan Efisiensi Pengelolaan Sumber Daya Air melalui Teknologi Cerdas: Studi Kasus di Wilayah Kashkadarya, Uzbekistan - Meyli Kizi, Abduhalimova Nafisa (Indonesian Journal of Innovation Studies, 2023)
This article presents a comprehensive study on the implementation of "Smart Water" devices in water management facilities in the Kashkadarya region of Uzbekistan. The goals of this initiative were to achieve efficient water control, real-time monitoring, and rapid water management. Through the installation of smart devices, including "Smart Water" devices and "DIVER" devices, water resources were effectively managed, resulting in online water control and significant water resource savings. The automation of large hydrotechnical facilities, such as the Karshi hydroelectric plant, enabled remote management and reduced technical water losses. Additionally, the pilot project on automation, based on solutions provided by the Australian company "Rubicon Water Pty. Ltd," showcased the potential for digitalization and automation in water resources management. The project demonstrated successful outcomes, including increased accuracy in land reclamation assessment, reduced water shortage, enhanced water resource utilization, and significant cost savings. The findings highlight the effectiveness and advantages of smart technologies in water management, underscoring the need for their widespread adoption in addressing water scarcity and sustainable water resource management globally. Highlights: Improved Water Control: Implementation of "Smart Water" devices enables real-time monitoring and online water control, enhancing efficient water resource management. Cost Savings and Resource Efficiency: Automation and smart technologies lead to significant water savings, reduced technical losses, and improved water utilization, resulting in economic benefits. Scalable Solutions for Global Water Management: The successful pilot project by "Rubicon Water Pty. Ltd" demonstrates the potential for widespread adoption of smart technologies in addressing water scarcity and promoting sustainable water resource management globally. Keywords: water resources, smart water, efficient technologies, water management, automation.